Effectiveness and safety of TNF inhibitors in adults with juvenile idiopathic arthritis. Issue 2 (7th October 2016) - Kearsley-Fleet, Lianne; McErlane, Flora; Foster, Helen E; Lunt, Mark; Watson, Kath D; Symmons, Deborah P M; Hyrich, Kimme L
Abstract : Introduction: Many children with juvenile idiopathic arthritis (JIA) continue to have active disease into adulthood. Adults with JIA are a heterogeneous group, and the effects of tumour necrosis factor inhibitor (TNFi) therapies are not well described. This analysis aims to describe treatment outcomes among patients with JIA starting TNFi for the first time in adulthood. Methods: Patients with arthritis onset <16 years starting their first TNFi therapy were identified from the British Society of Rheumatology Biologics Register. Disease activity outcomes (using 28-joint Disease Activity Score (DAS28) and Health Assessment Questionnaire (HAQ)) are presented at 1 year after start of therapy according to disease pattern. Incidence rates (IR) of adverse events per 1000 person-years (pyrs) were calculated. Outcomes in patients with polyarticular JIA were compared with a cohort (weighted for age and gender) of patients with rheumatoid arthritis (RA). Results: In 443 adults with JIA starting a first TNFi, disease activity over 1 year improved across all measures. There were 58 first serious infections (IR 22.3/1000 pyrs); 4 cardiovascular events (IR 1.4/1000 pyrs); 11 uveitis events (IR 4.0/1000 pyrs) and 16 malignancies (IR 3.9/1000 pyrs). Compared with the weighted RA cohort, disease activity improvement was similar; malignancy rates were lower and uveitis rates much higher. While crude IR were similar, JIA patients had a lower risk of serious infection (HR 0.5 (95% CI 0.3 to 0.9)). Conclusions: This is the largest study to describe disease activity and safety outcomes in adults with JIA receiving TNFi. Disease activity improved after 1 year in all disease patterns, suggesting TNFi is an effective therapy in this population.